What's Happened to Poverty and Inequality in Indonesia over Half a Century? - Hal Hill (Asian Development Review, 2021)
Indonesia has achieved moderately fast economic growth for most of the past 50 years. Has this growth translated into rising living standards? This is the question that is addressed in this paper. The conclusion is a qualified yes. The caveat is attached for two reasons: (i) philosophically, the definition of living standards remains a subject of considerable conjecture, and (ii) not all social indicators point in the same direction. I focus primarily on trends in measurable indicators of human welfare, particularly poverty and inequality. Combined with major improvements in the coverage and quality of the country's statistics, and a now extensive literature, it is possible to document, and in some cases explain, trends in living standards in some detail. I also investigate whether (and how) the sudden swing during 1999–2001 from an authoritarian and centralized regime to a democratic and decentralized era impacted significantly on these trends.